Multi-scale Simulation for Energy Flexible Factories and Factory Networks: A System of Systems Perspective - Siemon, Lukas; Blume, Christine; Mennenga, Mark; Herrmann, Christoph (Procedia CIRP, 2022)
The continuously increasing integration of volatile renewable energy sources requires an increasing amount of energy flexibility and organizational effort on the demand side to improve the synchronization of demand and supply. Within factories, energy flexibility potentials can be beneficially exploited to increase the utilization of on-site renewable energy. Excess renewable energy is usually fed into the grid for an ever decreasing feed-in compensation. Through the formation of local factory network as a collaborative systems of systems, factories can enhance the potentials of energy flexibility and on-site renewable energy. In this paper, the effects of two individual factories forming a collaborative factory network are evaluated regarding their potential to induce additional or amplified functionality for both factories. This functionality is quantified using environmental and economic indicators. A multi-scale multi-paradigm modeling approach is conducted to simulate and evaluate combined energy flexibility measures on single-factory level and on a collaborative factory network level. The results are discussed before the background of the definition of emergent behavior within systems of systems. Alongside the quantified results that support decision making for collaborative systems of systems, this work discusses the pain points of system of systems boundary definition and its impact on the definition and quantification of emergent behavior.